Formation of Socially Caring Character and Humble Behavior Through Arabic Language Learning in Islamic High Schools - Mahbub Humaidi Aziz; Ahmad Fadhel Syakir Hidayat; Isnainiyah Isnainiyah; Azwar Annas; Rifqi Aulia Rahman; Buhori Buhori; Bima Fandi Asy’arie (SCAD Independent, 2026)
The growing disconnect between academic achievement and students’ moral-social development has become a major challenge in contemporary Islamic education, particularly as character formation often remains detached from everyday classroom practice. Although Arabic language learning contains ethical, spiritual, and social dimensions rooted in Islamic traditions, it is still predominantly positioned as a technical-linguistic subject emphasizing grammar and language proficiency. This study aims to examine how Arabic language learning functions as a pedagogical medium for fostering social awareness and humble behavior among students in Islamic secondary schools. Employing a qualitative case study approach, this study involved 45 informants consisting of school leaders, Arabic language teachers, and students. Data were collected through classroom observations, semi-structured interviews, focus group discussions, and document analysis, and then analyzed using the interactive model of Huberman and Saldaña. The findings reveal that social awareness and humility are cultivated through value-oriented classroom interaction, reflective dialogue, collaborative learning, teachers’ role modeling, and school-based social activities integrated into Arabic language instruction. Ultimately, this study reconceptualizes Arabic language learning as a morally mediated social practice and positions Arabic teachers as moral agents shaping students’ ethical dispositions within Islamic educational contexts.